2020
DOI: 10.1038/s41564-020-0716-y
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional insights into oligopeptide acquisition by the RagAB transporter from Porphyromonas gingivalis

Abstract: Extended Data Fig. 2 RagAB binds a wide range of oligopeptides EDFig2.tiff a-c, LC-MS/MS analysis of peptides bound to RagAB W83 KRAB, showing length distribution (a), total charge (b) and pI (c). d-f, Analysis of peptides bound to RagAB W83 wild-type, showing length distribution (d), total charge (e) and pI (f). For charge calculations, the pH was assumed to be 7.0 and contributions of any His residues were ignored. g, Amino acid frequency of RagAB-bound peptides (KRAB and wild-type combined; black) vs. the a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(76 citation statements)
references
References 72 publications
1
75
0
Order By: Relevance
“…The SusD protein encoded within the starch utilization system locus of B. theta was the first in this protein family to be functionally characterized and validated as binding starch (Koropatkin et al, 2008;Shipman et al, 2000). Early work on the B. theta Sus provided direct evidence of an interaction between the SusC and SusD proteins, which has been validated in the recent crystal structures from homologous systems such as the levan BT1763/2 and the peptide-targeting BT2264/3 complexes (Glenwright et al, 2017;Gray et al, 2021;Madej et al, 2020;Shipman et al, 2000).…”
Section: Role Of the Susd Protein S In Bac Teroide Te Smentioning
confidence: 96%
“…The SusD protein encoded within the starch utilization system locus of B. theta was the first in this protein family to be functionally characterized and validated as binding starch (Koropatkin et al, 2008;Shipman et al, 2000). Early work on the B. theta Sus provided direct evidence of an interaction between the SusC and SusD proteins, which has been validated in the recent crystal structures from homologous systems such as the levan BT1763/2 and the peptide-targeting BT2264/3 complexes (Glenwright et al, 2017;Gray et al, 2021;Madej et al, 2020;Shipman et al, 2000).…”
Section: Role Of the Susd Protein S In Bac Teroide Te Smentioning
confidence: 96%
“…Multiple alignments showed that 10 sequences exhibited a conserved region of ~32 aa in the plug domain (Figure 2c) while the remaining five did not. The function of the Cpdr domain is not known but is located on the periplasmic side of the barrel in the RagA structure (Madej et al., 2020). Structural homology searches with Phyre‐2 for most P. gingivalis TDRs matched best to the ferripyoverdine receptor (FpvA) and the ferrioxamine b transporter (FoxA) of Pseudomonas aeruginosa .…”
Section: Resultsmentioning
confidence: 99%
“…Of the 15 predicted TDRs, only two have a definitive function. RagA (PG0185) was shown to complex with the RagB lipoprotein and was determined to be a peptide transporter based on structural studies, binding studies and growth experiments (Glew et al., 2014; Madej et al., 2020; Nagano et al., 2007). RagB serves as the initial peptide binder and also functions as a hinged lid on the extracellular side of RagA (Figure 2d).…”
Section: Resultsmentioning
confidence: 99%
“…Recent structures of SLP bipartite systems in Bacteroidetes involved in oligopeptide and glycan uptake (72,73) demonstrates that the field is expanding to include the study of SLPs that are involved in the uptake of nutrients that are not restricted by host specific proteins. Bacteroidetes possess enzymes that degrade complex, inaccessible sugars and proteins to produce simpler molecules more amenable to uptake for growth and perhaps signaling (72,73). Xray and cryo-electron microscopy structures coupled with functional studies support a model in which the Bacteroidetes starch utilization system (Sus) and receptor antigen gene (Rag) SLPs function as a lid that operates according to a pedal bin mechanism.…”
Section: Other Nutritional Bipartite Systemsmentioning
confidence: 99%